PENGARUH INFLASI, SUKU BUNGA, DAN HARGA MINYAK DUNIA TERHADAP INDEKS HARGA SAHAM GABUNGAN: Studi pada Bursa Efek Indonesia Periode 2018-2021 - Ni Komang Ayu Tulus Sawitri; Made Yudi Darmita; Made Christin Dwitrayani (Universitas Triatma Mulya, 2023)
Based on the development of the IHSG chart, there is a downward phenomenon from 2019 to 2020, this is comparable to the effect of the Coronavirus pandemic that hit Indonesia, causing the composite stock price index (IHSG) to experience a significant decline in 2020. One Economic factors that can have an impact on IHSG movements are inflation, interest rates and world oil prices. The definition of the issue and the reason for this study is to decide the fractional impact of inflation, interest rates and world oil prices on the IHSG for the 2018-2021 periods. The population and samples in this review were 48 samples utilizing the saturation sampling method. The information of analysis method in this review is Multiple Linier Regressions. In view of the exploration results, it very well may be seen that the inflation variable have a..negative impact on IHSG, the interest rate variable have a positive impactt on IHSG and world oil prices have a positive impact on IHSG. The extent of the effect of inflation, interest rates and world oil prices on IHSG was 81.2%, the leftover 18.8% was affected by different elements outside the models.